Decoloniality, Language, Identity and Communication: The Case Study of Cameroonian Pidgin (Global Journal of Human-Social Science, 2021)
In this paper, the intersection between decoloniality, language, identity and communication is discussed in how they come together in the use or refusal to use Cameroon Pidgin (CamP). The paper draws on the concepts of coloniality and decoloniality and relates them to language as used by Cameroonians in South Africa. The argument is that it is surprising that many Cameroonian Pidgin speaking immigrants are choosing not to communicate in Pidgin, especially since usage of the language from the home country could become a locus of solidarity and reproduction of one aspect of the everydayness of home in a new country. This article relies on a qualitative framework comprised of openended interviews, focus group discussions and participant observation to explore the role of language, identity and decoloniality in communication. The idea is to explore how these issues and themes intersect, and what the intersections themselves tell us, firstly, about the nature of identity and, secondly, about the relationship between language and identity.
Keywords: cameroon; cape town; south africa; camp; immigrant